Coronavirus pandemic and colorectal surgery: practical advice based on the Italian experience. (1st June 2020) - Di Saverio, S.; Pata, F.; Gallo, G.; Carrano, F.; Scorza, A.; Sileri, P.; Smart, N.; Spinelli, A.; Pellino, G.
Abstract: Aim: The current COVID‐19 pandemic is challenging healthcare systems at a global level. We provide a practical strategy to reorganize pathways of emergency and elective colorectal surgery during the COVID‐19 pandemic. Method: The authors, all from areas affected by the COVID‐19 emergency, brainstormed remotely to define the key‐points to be discussed. Tasks were assigned, concerning specific aspects of colorectal surgery during the pandemic, including the administrative management of the crisis in Italy. The recommendations (based on experience and on the limited evidence available) were collated and summarized. Results: Little is known about the transmission of COVID‐19, but it has shown a rapid spread. It is prudent to stop non‐cancer procedures and prioritize urgent cancer treatment. Endoscopy and proctological procedures should be performed highly selectively. When dealing with colorectal emergencies, a conservative approach is advised. Specific procedures should be followed when operating on COVID‐19‐patients, using dedicated personal protective equipment and adhering to specific rules. Some policies are described, including minimally‐invasive surgery. These policies outline the strict regulation of entry/ exit into theatres and operating building as well as advice on performing procedures safely to reduce risk of spreading the virus. It is likely that a reorganization of health system is required, both at central and local levels. A description of the strategy adopted in Italy is provided. Conclusion: Evidence on the management of patients needing surgery for colorectal conditions during the COVID‐19 pandemic is currently lacking. Lessons learnt from healthcare professionals that have managed high volumes of surgical patients during the pandemic could be useful to mitigate some risks and reduce exposure to other patients, public and healthcare staff.